The Nine-hued pheasant and the daughter-in-law of the poor: Raise of Consciousness in Women - Lamichhane, Bina (New Journey, 2023)
The major concern of this analytical research article is to pinpoint the issue of woman violence through the light of the poem. Violence is not a new term in connection to the problems of Nepali society. As a conscious member of the society, the poem entitled “The Nine-hued pheasant and the daughter-in-law of the poor” by the modern Nepali poet, Ahuti, drew my attention. So, to analyze the poem critically connecting its issue to the victimized women in our society is the main objective of the article. Nepali women have been facing such ill behaviour since ancient time. “Sati Pratha” can be taken as an example of brutal exploitation to women caused by so called orthodoxically patriarchal concept. Nepali women are still facing a number of social, cultural, and gender- related problems. How the poem entitled, “The Nine-hued pheasant and the daughter-in-law of the poor” deals with the issues regarding the problems of women in the society is the major concern of the article. . The major aspect of this article is to reflect the suffering of women in our society, violence against them, and their struggle to exist in the society and so no. As a qualitative research article, description, narration, explanation etc are the major tools to analyse the given text. In short, consciousness regarding women's position in the society is an important factor for women for getting justice. Instead of escaping from the problems, women should be bold to face them.